Effects of Resistance Training with Different Pyramid Systems on Bioimpedance Vector Patterns, Body Composition, and Cellular Health in Older Women: A Randomized Controlled Trial - Santos, Leandro dos; Ribeiro, Alex S.; Gobbo, Luis A. [UNESP]; Nunes, Joao Pedro; Cunha, Paolo M.; Campa, Francesco; Toselli, Stefania; Schoenfeld, Brad J.; Sardinha, Luis B.; Cyrino, Edilson S. (Mdpi, 2020)
Bioelectrical impedance vector analysis (BIVA) and phase angle (PhA) have been widely used to monitor changes in health-related parameters in older adults, while resistance training (RT) is one of the potential strategies to mitigate the adverse effects of aging. The purpose of this study was to compare the effects of the crescent pyramid RT system with two repetition zones on BIVA patterns and PhA. Fifty-five older women (>= 60 years) were randomly assigned into three groups: control (CON, n = 18), narrow pyramid (NPR, n = 19), and wide pyramid (WPR, n = 18). The RT was performed for eight weeks, three times per week, in eight exercises for the whole body with three sets of 12/10/8 (NPR) or 15/10/5 repetitions (WPR). Bioimpedance spectroscopy (50 kHz frequency) was assessed. After the intervention period, both training groups showed significant changes in BIVA patterns compared to CON (p< 0.001); resistance decreased and reactance increased, which resulted in a BIVA-vector displacement over time (p< 0.001). Changes in PhA were greater for WPR ( increment % = 10.6; effect size [ES] = 0.64) compared to NPR ( increment % = 5.3; ES = 0.41) and CON ( increment % = -6.4; ES = -0.40). The results suggest that the crescent pyramid RT system with both repetition zones (WPR and NPR) is effective for inducing improvements in BIVA patterns and PhA in older women, although WPR elicits greater increases in PhA than NPR.
Keywords: aging; BIVA; bioelectrical impedance analysis; body composition; elderly; strength training; dose-response